Molecular Hybrids of N-Phthaloylglycyl Hydrazide and Hydrazinecarbothioamide with Anti-inflammatory and Anti-oxidant Activities - Gera, Ankur; Mohan, Chander; Madan, Jitender; Arora, Sandeep (Current Organic Synthesis, 2019)
Background: Oxidative stress due to high levels of reactive organic species is the cause of the progression of inflammation in various diseases. The molecules possessing both anti-inflammatory and antioxidant activity can be the promising key to treat inflammatory diseases. Phthalimide and hydrazinecarbothioamide are anti-inflammatory and anti-oxidant pharmacophores. Objective: Molecular hybrids possessing above two pharmacophores were designed. A series of N-phenyl substituted 2-(2-(1,3-dioxoisoindolin-2-yl)acetyl)-N-phenylhydrazine-1-carbothioamide (CGS compounds) was synthesized and evaluated for biological activities. Methods: N-phthaloylglycyl hydrazide was reacted with unsubstituted/substituted phenyl isothiocyanates to yield CGS compounds. Synthesized compounds were evaluated for in vivo anti-inflammatory activity in carrageenan rat paw edema model, and in vitro anti-oxidant activity by DPPH assay. Levels of TNF-α and oxidative stress at the site of inflammation were measured. The genetic algorithm-PLS regression based QSAR model correlating the effect of N-phenyl substituent on the anti-inflammatory activity was developed. Further, the interaction of the active compound in the TNF-α binding pocket was studied by in silico docking. Results: Compound containing the 2-OCH3, 4-NO2 (CGS-5); 4-CF3 (CGS-9); 4-NO2 (CGS-3) showed significant anti-inflammatory activity (percentage inhibition of paw edema after 3 hour = 58.24, 50.38, 40.05, respectively) and potent anti-oxidant activity (IC50 =0.045, 0.998, 0.285 μg/ml, respectively). Reduced levels of TNF- α and increased levels of GSH were observed for the above three compounds. Descriptors for QSAR model identified by GA-PLS were WPSA1, Weta1unity, WDunity, SC3, VC5, MlogP, and WTPT3. The identified model was highly predictive, and value of root mean square error of prediction for internal (leave one out) and external validation was: 1.579, 1.325. Conclusion: Molecular hybrids of phthalimide and hydrazinecarbothioamide were synthesized. Some of the compounds possessed promising anti-inflammatory and anti-oxidant activities.
Keywords: anti-oxidant